(untitled) (Revista Contexto & Saúde, 2025)
Parkinson’s Disease (PD) results in the reduction of the individual’s independence and functionality. Physiotherapy acts in the management of PD based on several strategies, such as health education. The objective of this study was to identify, analyze and develop innovative and educational content in health and analyze the metrics achieved in social networks. The research is exploratory, explanatory of content analysis and descriptive of data collection, divided into 6 phases: 1. Search for thematic materials on PD, 2. Definition of content to be produced, 3. Development of scripts, 4. Technical production, 5. Disclosure and 6. Analysis of metrics achieved. Most of the content found is of the generalist information type and the result of the achieved metrics yielded 373 views. It is necessary to advance in health education, mainly in the quality and depth of information